Concordance between self-reported body mass index with weight perception, self-rated health and appearance satisfaction in people living in Tehran. Issue 1 (December 2015) - Haghighian Roudsari, Arezoo; Vedadhir, Abouali; Kalantari, Naser; Amiri, Parisa; Omidvar, Nasrin; Eini-Zinab, Hassan; pouri Hosseini, Seyed
Abstract Background Obesity is investigated as a health concern due to high prevalence in the world. Nowadays, researchers are looking for an indirect method to measure weight and height. Self-reported Body Mass Index (BMI) is ever more served as an alternative method for direct weight and height measurement. Misreporting is a usual concern in self-reported BMI, thus, this study set explored the association and degree of agreement of self-reported BMI with weight perception, Self-Rated Health (SRH), and appearance satisfaction in people living in Tehran, Iran. Methods 722 men and women (268 men and 454 women) aged 30–64 years were selected using Cluster Multi-stage Sampling with the Probability Proportional to Size (PPS) method from each area. The questionnaire included demographic and socioeconomic variables and self-reported weight and height and questions related to weight and health perception, and appearance satisfaction. Independent samplesT -test compared the mean of scales and differences in characteristics between BMI categories, analyzed using chi-square test. TheCohen's kappa coefficient examined the association between self-reported BMI and weight perception, SRH, and appearance satisfaction. Results The mean self-reported weight was 80.79 ± 12.87 in men and 68.33 ± 11.53 in women. The results of the agreement analysis for weight perception were Kappa = 0.38 withp <  0.0001 for women and Kappa = 0.23 withp < 0.0001 for men. This measure of agreement, while statistically significant, is fair agreement. SRH and appearance satisfaction were not significantly correlated with self-reported BMI. Conclusion The measurements of height and weight can cause significant imprecisions in calculation of BMI, which is used as a guide for identifying persons at risk of disease. Direct measurement of height and weight should be performed whenever possible for optimal measurements in clinical practice and clinically oriented researches.